Formal synthesis of (−)-agelastatin A: an iron(II)-mediated cyclization strategy - Shigeoka, Daisuke; Kamon, Takuma; Yoshimitsu, Takehiko (Beilstein Journal of Organic Chemistry, 2013)
An iron(II)-mediated aminohalogenation of a cyclopentenyl N-tosyloxycarbamate provided new access to the key intermediate for the synthesis of (−)-agelastatin A (AA, 1), a potent antiproliferative alkaloid. The present synthetic endeavour offered an insight into the mechanism underlying the iron(II)-mediated aminohalogenation of N-tosyloxycarbamate, in which the radical properties of the N–iron intermediates in the redox states were operative.
Keywords: agelastatin; aminohalogenation; iron(II); free radical; natural product synthesis

(untitled) - D’Ambrosio, M.; Guerriero, A.; Debitus, C.; Ribes, O.; Pusset, J.; Leroy, S.; Pietra, F. (J. Chem. Soc., Chem. Commun., 1993)

(untitled) - Hong, T. W.; Jímenez, D. R.; Molinski, T. F. (J. Nat. Prod., 1998)

(untitled) - Tilvi, S.; Moriou, C.; Martin, M.-T.; Gallard, J.-F.; Sorres, J.; Patel, K.; Petek, S.; Debitus, C.; Ermolenko, L.; Al-Mourabit, A. (J. Nat. Prod., 2010)

(untitled) - Pettit, G. R.; Ducki, S.; Herald, D. L.; Doubek, D. L.; Schmidt, J. M.; Chapuis, J.-C. (Oncol. Res., 2005)

(untitled) - Mason, C. K.; McFarlane, S.; Johnston, P. G.; Crowe, P.; Erwin, P. J.; Domostoj, M. M.; Campbell, F. C.; Manaviazar, S.; Hale, K. J.; El-Tanani, M. (Mol. Cancer Ther., 2008)

(untitled) - Stien, D.; Anderson, G. T.; Chase, C. E.; Koh, Y.-H.; Weinreb, S. M. (J. Am. Chem. Soc., 1999)

(untitled) - Feldman, K. S.; Saunders, J. C. (J. Am. Chem. Soc., 2002)

(untitled) - Hale, K. J.; Domostoj, M. M.; Tocher, D. A.; Irving, E.; Scheinmann, F. (Org. Lett., 2003)

(untitled) - Domostoj, M. M.; Irving, E.; Scheinmann, F.; Hale, K. J. (Org. Lett., 2004)

(untitled) - Davis, F. A.; Deng, J. (Org. Lett., 2005)

(untitled) - Trost, B. M.; Dong, G. (J. Am. Chem. Soc., 2006)

(untitled) - Ichikawa, Y.; Yamaoka, T.; Nakano, K.; Kotsuki, H. (Org. Lett., 2007)

(untitled) - Dickson, D. P.; Wardrop, D. J. (Org. Lett., 2009)

(untitled) - Wehn, P. M.; Du Bois, J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Hama, N.; Matsuda, T.; Sato, T.; Chida, N. (Org. Lett., 2009)

(untitled) - Movassaghi, M.; Siegel, D. S.; Han, S. (Chem. Sci., 2010)

(untitled) - Menjo, Y.; Hamajima, A.; Sasaki, N.; Hamada, Y. (Org. Lett., 2011)

(untitled) - Reyes, J. C. P.; Romo, D. (Angew. Chem., Int. Ed., 2012)

(untitled) - Kano, T.; Sakamoto, R.; Akakura, M.; Maruoka, K. (J. Am. Chem. Soc., 2012)

Strategies and Tactics in Organic Synthesis - Hale, K. J.; Domostoj, M. M.; El-Tanani, M.; Campbell, F. C.; Mason, C. K. (Academic Press, 2005)
See for selected reviews of agelastatins and related compounds.

(untitled) - Weinreb, S. M. (Nat. Prod. Rep., 2007)

(untitled) - Dong, G. (Pure Appl. Chem., 2010)

(untitled) - Young, I. S.; Thornton, P. D.; Thompson, A. (Nat. Prod. Rep., 2010)

(untitled) - Al-Mourabit, A.; Zancanella, M. A.; Tilvi, S.; Romo, D. (Nat. Prod. Rep., 2011)

(untitled) - Yamaoka, T.; Ichikawa, Y.; Kotsuki, H. (J. Synth. Org. Chem., Jpn., 2012)

(untitled) - Yoshimitsu, T.; Ino, T.; Tanaka, T. (Org. Lett., 2008)

(untitled) - Yoshimitsu, T.; Ino, T.; Futamura, N.; Kamon, T.; Tanaka, T. (Org. Lett., 2009)

(untitled) - Kamon, T.; Shigeoka, D.; Tanaka, T.; Yoshimitsu, T. (Org. Biomol. Chem., 2012)

(untitled) - Nguyen, Q.; Nguyen, T.; Driver, T. G. (J. Am. Chem. Soc., 2013)
See for a recent application of catalytic FeBr2 to C–H amination.

(untitled) - Bach, T.; Schlummer, B.; Harms, K. (Chem. Commun., 2000)

(untitled) - Bach, T.; Schlummer, B.; Harms, K. (Synlett, 2000)

(untitled) - Bach, T.; Schlummer, B.; Harms, K. (Chem.–Eur. J., 2001)

(untitled) - Churchill, D. G.; Rojas, C. M. (Tetrahedron Lett., 2002)

(untitled) - Bacci, J. P.; Greenman, K. L.; Van Vranken, D. L. (J. Org. Chem., 2003)

(untitled) - Danielec, H.; Klügge, J.; Schlummer, B.; Bach, T. (Synthesis, 2004)

(untitled) - Lebel, H.; Huard, K.; Lectard, S. (J. Am. Chem. Soc., 2005)

(untitled) - King, E. R.; Hennessy, E. T.; Betley, T. A. (J. Am. Chem. Soc., 2011)
See for recent studies on C–H cleavage by N–iron complex showing radical character.

(untitled) - Paradine, S. M.; White, M. C. (J. Am. Chem. Soc., 2012)
and references cited therein.

(untitled) - Ton, T. M. U.; Tejo, C.; Tania, S.; Chang, J. W. W.; Chan, P. W. H. (J. Org. Chem., 2011)

(untitled) - Maestre, L.; Sameera, W. M. C.; Mar Díaz-Requejo, M.; Maseras, F.; Pérez, P. J. (J. Am. Chem. Soc., 2013)
See for a recent discussion on the mechanisms of metal–nitrenide catalysis.